2020
DOI: 10.31235/osf.io/pz5vn
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Hotel managers’ perceptions towards the use of robots: a mixed-methods approach

Abstract: Adopting a supply-side perspective, the present paper analyses Bulgarian hotel managers’ perceptions of service robots using a convergent mixed methods design. Structured quantitative data was collected from 79 hotel managers through a questionnaire, while interviews were used for the collection of qualitative data from 20 hotel managers. The findings indicate that repetitive, dirty, dull, and dangerous tasks in hotels would be more appropriate for robots, while hotel managers would rather use human employees … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
30
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(31 citation statements)
references
References 58 publications
1
30
0
Order By: Relevance
“…Although previous research analyzed customer attitudes toward service robots in the general service context [ 37 , 87 , 88 , 89 ], little research has taken the context of public health emergencies into account. This research aimed to discuss the effect of perceived risk on customer–robot engagement in a public health emergency.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although previous research analyzed customer attitudes toward service robots in the general service context [ 37 , 87 , 88 , 89 ], little research has taken the context of public health emergencies into account. This research aimed to discuss the effect of perceived risk on customer–robot engagement in a public health emergency.…”
Section: Discussionmentioning
confidence: 99%
“…Further, customers will pay more attention to service robots, show more enthusiasm towards service robots, and have more interaction with service robots. Before the COVID-19 pandemic, most researchers found that customers preferred service to be provided by human staff rather than by service robots [ 37 , 87 , 88 , 89 ]. Some research on anthropomorphism argued that anthropomorphized robots could reduce resistance from customers [ 84 , 85 ].…”
Section: Discussionmentioning
confidence: 99%
“…Despite the benefits that the concept of Society 5.0 and the application of UAS present, there is a factor which produces doubt and scepticism from different management perspectives on its execution. In terms of the society 5.0 concept, the identified barriers for its adoption in society are oriented by legal aspects, acceptance of working along robots, mental disorders, human substitution, organisational changes on human resource departments, ethics on robots, human competition with robots and business cases (Ivanov, et al, 2020;Demir, et al, 2019;.…”
Section: Barriers Of Society 50 and Unmanned Aerial Systemsmentioning
confidence: 99%
“…Ivanof et al (2020) have used triangulation in a sample made from hotel managers in Bulgaria. The findings of Ivanov et al (2020) indicate that hotel managers would like to use robots on dangerous and dull tasks in hotels, while human employees would be rather used on tasks which require soft skills and emotional intelligence. An important finding in this research is that the hotel managers regard that robots will decrease service quality of the hotels and that human workforce is much more valuable than robots; for this reason they seem not to favour the use of robots on their premises and they do no have the intention to use robots especially on risky tasks, though a meta-analysis made from Belias (2020b) argues that robots may leverage service quality of hotels and that the hotel managers and employees shall have high expectations.…”
Section: The Use Of Robots In the Tourism Industrymentioning
confidence: 99%
“…At this point it should be noted also that there is a research gap in the acceptance of robots α by the public and employees in hotel units, while ther are different views on the impact on robots on services quality (ie. Belias, 2020b andIvanov et al 2020) while affects the intention to use robots. For this reason, the authors have constructed a research model which may fill in the existing gap.…”
Section: The Use Of Robots In the Tourism Industrymentioning
confidence: 99%